Near-alpha titanium alloy and preparation and application thereof
Through the combination of solid solution heat treatment and aging heat treatment, the precipitation of nano-scale silicides is regulated, which solves the problem of insufficient creep performance of high-temperature titanium alloys at high temperatures, and achieves the improvement of high-temperature performance and thermal stability of titanium alloys.
Patent Information
- Application Number
- CN202510035373.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-21
AI Technical Summary
The existing high-temperature titanium alloys have insufficient creep performance at high temperatures, and the uneven precipitation of nano-scale silicides affects the strength and plasticity of the alloy.
Through the combination of solid solution heat treatment and aging heat treatment, it is ensured that all nano-scale silicides are dissolved in the titanium alloy matrix, and the number and distribution of their precipitation are regulated at a specific temperature, so as to achieve the goal of improving the high-temperature creep resistance of high-temperature titanium alloys.
The high-temperature performance of titanium alloy is improved, its high-temperature creep resistance and thermal stability are enhanced, and the comprehensive mechanical properties of the alloy are improved.
Smart Images

Figure CN119663053A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy structure regulation, and in particular to a near-alpha titanium alloy and preparation and application thereof. Background Art
[0002] Since high-temperature titanium alloys are mainly used in the aerospace field, they not only need to have instantaneous high strength at room temperature and high temperature conditions, but also must show excellent high-temperature creep resistance, long-lasting strength and microstructural stability. High-temperature titanium alloys are divided into two types: near-α type and α+β type. When the service temperature reaches 500°C, near-α type high-temperature titanium alloys (also called "near-α titanium alloys") are preferred.
[0003] The creep rupture properties of near-α titanium alloys are significantly affected by the precipitation phase. In near-α titanium alloys, there are usually two key precipitation phases: silicide (TiSi phase) and α 2 Phase (Ti 3 Al ordered phase). 2 The phase plays a significant role in improving the deformation resistance of the alloy, while the solid solution silicon and silicide have a positive effect on the creep performance of the alloy at high temperature. The solid solution Si has a solid solution strengthening effect on the titanium alloy, and the silicide precipitation phase has a precipitation strengthening effect on the titanium alloy. Silicides are divided into three structures, namely (Ti, Zr) 5 Si 3 (S1 type), (Ti, Zr) 6 Si 3 (S2 type), (Ti, Zr) 3 Si (S3 type). The precipitation mechanism of silicide is related to factors such as alloy composition, thermal processing technology and heat treatment system. The aging treatment temperature has a great influence on the precipitation, distribution, morphology and particle size of nano-scale silicide.
[0004] Nano-scale silicides are mainly precipitated at the interface between the equiaxed α phase and the β transformation structure and the interface between the α / β sheets in the β transformation structure. They are spherical or ellipsoidal in shape and about 60 to 100 nm in size. Fine and dispersed silicides are beneficial to the strength of the alloy, but as the number of silicides precipitated increases and the distribution is uneven, the strength and plasticity of the alloy will be significantly reduced. In order to pursue the high-temperature creep resistance of high-temperature titanium alloys, the precipitation and growth process of nano-scale silicides must be effectively controlled.
[0005] Patent CN116144980A discloses the control of silicide and its precipitation growth of high-temperature titanium alloy. By adding 0.28-0.5wt.% silicon element to the high-temperature titanium alloy, it is ensured that part of the Si element is dissolved in the matrix and the other part is precipitated in the β phase between the lamellar α phase in the form of silicide. Through the double heat treatment process of 1030℃ / 1h~3h / air cooling + 600℃~850℃ / 2h~4h / air cooling, the silicide is coordinated and controlled to regulate the precipitation amount of silicide in the high-temperature titanium alloy. Through the solid solution strengthening of silicon and the precipitation strengthening of silicide, the thermal strength goal of improving the creep resistance of titanium alloy is achieved. This process is used for Ti-Al-Sn-Zr-Mo-Nb-Ta titanium-based alloys used for a long time at temperatures of 500℃ and above, and adopts a double heating-insulation-air cooling heat treatment method. However, the two-stage air cooling method adopted in this process is not conducive to the refinement of the structure during the solution process. The thickness of the lamellar α phase in the β transformation structure will increase with the slowing down of the cooling rate, and the size of the equiaxed α phase will also increase with the decreasing of the cooling rate.
[0006] Therefore, it is of great significance to provide a method for regulating the precipitation of nano-scale silicides to improve the high-temperature properties of near-α titanium alloys. Summary of the invention
[0007] In order to solve the above problems, the purpose of the present invention is to provide a near-α titanium alloy and its preparation and application. In the present invention, the solution heat treatment is used to dissolve all the nano-scale silicides in the alloy ingot into the titanium alloy matrix; the aging heat treatment is used to control the amount and distribution of nano-scale silicide precipitation; the present invention achieves the goal of improving the high-temperature performance of the near-α titanium alloy through the solid solution strengthening of silicon and the precipitation strengthening of silicides.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The first object of the present invention is to provide a method for preparing a near-α titanium alloy, comprising the following steps:
[0010] The alloy ingot is subjected to solution heat treatment and aging heat treatment in sequence to obtain a near-α titanium alloy;
[0011] The alloy ingot comprises the following chemical components in mass percentage:
[0012] Al: 5.2-6.2%, Sn: 3.6-5.6%, Zr: 3.5-5.0%, Ta: 0.5-2.5%, W: 0.2-1.5%, Si: 0.2-0.6%, Nb: 0.2-0.5%, single impurity ≤ 0.05%, total impurities ≤ 0.25%, the rest is Ti;
[0013] The solution heat treatment is used to dissolve all the nano-scale silicides in the alloy ingot into the titanium alloy matrix;
[0014] The aging heat treatment is used to control the amount and distribution of nano-scale silicide precipitation, and to exert the precipitation strengthening effect of silicide, thereby achieving the goal of improving the high-temperature creep resistance of high-temperature titanium alloy.
[0015] When the heating temperature exceeds 1040°C, all the silicides are dissolved and all the silicon elements are dissolved in the matrix; then when the heating temperature reaches 700°C, nano-scale silicides begin to precipitate at the interface between the equiaxed α phase and the β transformation structure and at the interface between the α / β sheets in the β transformation structure. The largest number of nano-scale silicides precipitate at 750°C.
[0016] In one embodiment of the present invention, during the solution heat treatment, the specific process is: keeping at 1015-1025°C for more than 2h, and cooling with water after leaving the furnace;
[0017] Preferably, during the solution heat treatment, the specific process is: keeping at 1020°C for 2 hours and water cooling after taking out of the furnace.
[0018] In one embodiment of the present invention, during the aging heat treatment, the specific process is: keeping at 695-705°C for more than 5 hours, and air cooling after leaving the furnace;
[0019] Preferably, during the aging heat treatment, the specific process is: keeping at 700°C for 5 hours and air cooling after leaving the furnace.
[0020] In the present invention, a water cooling + air cooling method is adopted to change the arrangement of α / β sheets from neat bundles to randomly distributed strips. The room temperature ultimate tensile strength and yield strength, 650°C high temperature tensile strength and plasticity of the water-cooled sample after solid solution are significantly higher than those of the air-cooled sample after solid solution. On the other hand, W is a eutectoid β element in titanium alloy, and its eutectoid reaction temperature is as high as 715°C. 0.2-1.5% W is added to the near-α titanium alloy in the present invention, so that it has better thermal stability and higher thermal strength performance than the alloy in patent CN116144980A.
[0021] In one embodiment of the present invention, the alloy ingot is prepared by the following method:
[0022] Sponge titanium, aluminum, tin, sponge zirconium, tungsten, tantalum, niobium and silicon are pressed into a mixed block, and heated and melted in a sealed melting chamber to obtain an alloy ingot.
[0023] In one embodiment of the present invention, before heating, the melting chamber is evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0024] The second object of the present invention is to provide a near-α titanium alloy prepared by the above method.
[0025] The third object of the present invention is to provide an application of a near-α titanium alloy in the preparation of aerospace materials.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention utilizes the strengthening effect of silicide to improve the high temperature creep resistance of high temperature titanium alloy;
[0028] (2) The present invention adjusts the size and amount of silicide precipitation through solid solution and aging heat treatment of 1020℃ / 2h / water cooling + 700℃ / 5h / air cooling, achieves coordinated control of silicides, matches the thermal stability and thermal strength of near-α titanium alloys, and improves the comprehensive mechanical properties of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The microstructure of the alloy ingot of Example 1 after solution heat treatment (1020°C / 2h / water cooling);
[0030] Figure 2 This is a precipitation morphology of nano-scale silicide after the alloy ingot of Example 1 was subjected to solution heat treatment (1020°C / 2h / water cooling) and aging heat treatment (700°C / 5h / air cooling);
[0031] Figure 3 This is a precipitation state diagram of the alloy ingot of Example 1 at the triple grain boundary after solution heat treatment (1020°C / 2h / water cooling) and aging heat treatment (700°C / 5h / air cooling);
[0032] Figure 4 The microstructure of the alloy ingot of Comparative Example 1 after solution heat treatment (1020°C / 2h / water cooling) and aging heat treatment (650°C / 5h / air cooling);
[0033] Figure 5 It is a precipitation state diagram of the alloy ingot of Comparative Example 2 after solution heat treatment (1020°C / 2h / water cooling) and aging heat treatment (750°C / 5h / air cooling);
[0034] Figure 6 This is the microstructure diagram of the alloy ingot sample of Comparative Example 3 that was not subjected to heat treatment. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] In the following examples, unless otherwise specified, all reagents used are commercially available reagents, and all detection means and methods used are conventional detection means and methods in the art.
[0037] Example 1
[0038] This embodiment provides a method for preparing a near-α titanium alloy, comprising the following steps:
[0039] (S1) Preparation of alloy ingots: The alloy ingots are prepared in a vacuum induction melting furnace. The raw materials are sponge titanium (purity of 99.80wt.%), aluminum (purity of 99.99wt.%), tin (purity of 99.90wt.%), sponge zirconium (purity of 99.40wt.%), tungsten (purity of 99.95wt.%), tantalum (purity of 99.95wt.%), niobium (purity of 99.95wt.%) and silicon (purity of 99.50wt.%). In order to ensure the melting efficiency and uniformity of the alloy composition, the raw materials are mixed into blocks by a pressing device before melting, and then melted in a sealed melting chamber. The controlled atmosphere in the melting chamber is dry high-purity argon (99.999%); before heating, the melting chamber is evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0040] (S2) Preparation of near-α titanium alloy: The alloy ingot is subjected to solution heat treatment (keeping at 1020°C for 2 hours, water cooling after being taken out of the furnace) and aging heat treatment (keeping at 700°C for 5 hours, air cooling after being taken out of the furnace) in sequence to obtain a near-α titanium alloy.
[0041] Among them, the near-α titanium alloy includes the following chemical compositions by mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, individual impurities ≤ 0.05%, total impurities ≤ 0.25%, and the rest is Ti. The β phase transition temperature is about 1040°C.
[0042] The microstructure of the near-α titanium alloy prepared in this embodiment was observed (eg Figures 1 to 3 As shown) and high temperature mechanical properties test at 650℃.
[0043] pass Figure 1 It can be found that there is no precipitation phase after 1020℃ / 2h / water cooling treatment; Figure 2 and Figure 3 It can be found that after 1020℃ / 2h / water cooling treatment and then 700℃ / 5h / air cooling treatment, nano-scale silicide precipitation was observed ( Figure 2), the precipitation of nano-scale silicide occurs in the α / β sheets between the β transformation structures and the triple grain boundaries between the equiaxed α phase and the β transformation structures. The number of silicide precipitation phases is the largest at the triple grain boundaries between the equiaxed α phase and the β transformation structures ( Figure 3 ).
[0044] The near-α titanium alloy prepared in this embodiment was subjected to a high temperature mechanical property test at 650° C. The results showed that the yield strength was 595.7 MPa, the tensile strength was 659.0 MPa, and the elongation after fracture was 36%.
[0045] Comparative Example 1
[0046] This comparative example provides a method for preparing a titanium alloy, comprising the following steps:
[0047] (S1) Preparation of alloy ingots: The alloy ingots were prepared in a vacuum induction melting furnace. The raw materials were sponge titanium (purity 99.80wt.%), aluminum (99.99wt.%), tin (99.90wt.%), sponge zirconium (99.40wt.%), tungsten (99.95wt.%), tantalum (99.95wt.%), niobium (99.95wt.%) and silicon (99.50wt.%). To ensure the melting efficiency and uniformity of the alloy composition, the raw materials were mixed into blocks by a pressing device before melting, and then melted in a sealed melting chamber. The controlled atmosphere in the melting chamber was dry high-purity argon (99.999%). Before heating, the melting chamber was evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0048] (S2) Preparation of titanium alloy: The alloy ingot is subjected to solution heat treatment (keeping at 1020°C for 2 hours, water cooling after being taken out of the furnace) and aging heat treatment (keeping at 650°C for 5 hours, air cooling after being taken out of the furnace) in sequence to obtain a titanium alloy.
[0049] The titanium alloy includes the following chemical compositions by mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, individual impurities ≤ 0.05%, total impurities ≤ 0.25%, and the rest is Ti. The β phase transition temperature is about 1040°C.
[0050] The titanium alloy prepared in this comparative example was subjected to microstructural observation (such as Figure 4 As shown) and high temperature mechanical properties test at 650℃.
[0051] pass Figure 4It can be found that no precipitation of nano-scale silicide is observed after 1020°C / 2h / water cooling treatment and then 650°C / 5h / air cooling treatment, indicating that the nano-scale silicide cannot precipitate from the matrix due to the too low aging temperature.
[0052] The titanium alloy prepared in this comparative example was subjected to a high temperature mechanical property test at 650°C. The results showed that the yield strength was 630.2 MPa, the tensile strength was 699.7 MPa, and the elongation after fracture was 28%, indicating that after aging treatment at 650°C, the elongation was much lower than that after aging treatment at 700°C.
[0053] Comparative Example 2
[0054] This comparative example provides a method for preparing a titanium alloy, comprising the following steps:
[0055] (S1) Preparation of alloy ingots: The alloy ingots were prepared in a vacuum induction melting furnace. The raw materials were sponge titanium (purity 99.80wt.%), aluminum (99.99wt.%), tin (99.90wt.%), sponge zirconium (99.40wt.%), tungsten (99.95wt.%), tantalum (99.95wt.%), niobium (99.95wt.%) and silicon (99.50wt.%). To ensure the melting efficiency and uniformity of the alloy composition, the raw materials were mixed into blocks by a pressing device before melting, and then melted in a sealed melting chamber. The controlled atmosphere in the melting chamber was dry high-purity argon (99.999%). Before heating, the melting chamber was evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0056] (S2) Preparation of titanium alloy: The alloy ingot is subjected to solution heat treatment (keeping at 1020°C for 2 hours, water cooling after being taken out of the furnace) and aging heat treatment (keeping at 750°C for 5 hours, air cooling after being taken out of the furnace) in sequence to obtain a titanium alloy.
[0057] The titanium alloy includes the following chemical compositions by mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, individual impurities ≤ 0.05%, total impurities ≤ 0.25%, and the rest is Ti. The β phase transition temperature is about 1040°C.
[0058] The titanium alloy prepared in this comparative example was subjected to microstructural observation (eg Figure 5 As shown) and high temperature mechanical properties test at 650℃.
[0059] pass Figure 5It can be found that a large amount of nano-scale silicide precipitation is observed after 1020°C / 2h / water cooling treatment and then 750°C / 5h / air cooling treatment, indicating that the aging temperature is too high, resulting in excessive precipitation of nano-scale silicide.
[0060] The titanium alloy prepared in this comparative example was subjected to a high temperature mechanical property test at 650°C. The results showed that the yield strength was 578.7 MPa, the tensile strength was 644.7 MPa, and the elongation after fracture was 24%, indicating that after aging treatment at 750°C, the elongation was lower than that after aging treatment at 700°C and the strength also decreased.
[0061] Comparative Example 3
[0062] This comparative example provides a method for preparing a titanium alloy, comprising the following steps:
[0063] (S1) Preparation of alloy ingots: The alloy ingots were prepared in a vacuum induction melting furnace. The raw materials were sponge titanium (purity 99.80wt.%), aluminum (99.99wt.%), tin (99.90wt.%), sponge zirconium (99.40wt.%), tungsten (99.95wt.%), tantalum (99.95wt.%), niobium (99.95wt.%) and silicon (99.50wt.%). To ensure the melting efficiency and uniformity of the alloy composition, the raw materials were mixed into blocks by a pressing device before melting, and then melted in a sealed melting chamber. The controlled atmosphere in the melting chamber was dry high-purity argon (99.999%). Before heating, the melting chamber was evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0064] (S2) Preparation of titanium alloy: The alloy ingots were subjected to solution heat treatment (1020° C. for 2 h and water-cooled after being taken out of the furnace) to obtain a titanium alloy.
[0065] The titanium alloy includes the following chemical compositions by mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, individual impurities ≤ 0.05%, total impurities ≤ 0.25%, and the rest is Ti. The β phase transition temperature is about 1040°C.
[0066] The titanium alloy prepared in this comparative example was subjected to microstructural observation (such as Figure 1 As shown) and high temperature mechanical properties test at 650℃.
[0067] pass Figure 1 It can be found that no nano-scale silicide precipitation is observed after treatment at 1020°C / 2h, indicating that the silicon element exists in the form of solid solution after solid solution and cannot precipitate from the matrix.
[0068] The titanium alloy prepared in this comparative example was subjected to a high temperature mechanical properties test at 650°C. The results showed that the yield strength was 636.1 MPa, the tensile strength was 732.6 MPa, and the elongation after fracture was 31%, indicating that after 1020°C solution treatment, the strength was slightly higher than that after 700°C aging treatment, but the elongation was lower than that after 700°C aging treatment.
[0069] Comparative Example 4
[0070] This comparative example provides a method for preparing a titanium alloy, comprising the following steps:
[0071] Titanium alloy is prepared by vacuum induction melting furnace, and the raw materials are sponge titanium (purity 99.80wt.%), aluminum (99.99wt.%), tin (99.90wt.%), sponge zirconium (99.40wt.%), tungsten (99.95wt.%), tantalum (99.95wt.%), niobium (99.95wt.%) and silicon (99.50wt.%). In order to ensure the melting efficiency and uniformity of alloy composition, the raw materials are mixed into blocks by pressing equipment before melting, and then melted in a sealed melting chamber. The controlled atmosphere in the melting chamber is dry high-purity argon (99.999%); before heating, the melting chamber is evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0072] The titanium alloy includes the following chemical compositions by mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, individual impurities ≤ 0.05%, total impurities ≤ 0.25%, and the rest is Ti. The β phase transition temperature is about 1040°C.
[0073] The titanium alloy prepared in this comparative example was subjected to microstructural observation (eg Figure 6 As shown) and high temperature mechanical properties test at 650℃.
[0074] pass Figure 6 It can be found that this comparative example does not undergo any heat treatment and no nano-scale silicide precipitation phase is precipitated.
[0075] The titanium alloy prepared in this comparative example was subjected to a high temperature mechanical property test at 650°C. The results showed that the yield strength was 480.7 MPa, the tensile strength was 528.9 MPa, and the elongation after fracture was 23%, indicating that without any heat treatment, the strength and plasticity were lower than those after 700°C aging treatment.
[0076] Comparative Example 5
[0077] This comparative example provides a method for preparing a titanium alloy, comprising the following steps:
[0078] ((S1) Preparation of alloy ingots: The alloy ingots were prepared by vacuum induction melting furnace. The raw materials were sponge titanium (purity 99.80wt.%), aluminum (99.99wt.%), tin (99.90wt.%), sponge zirconium (99.40wt.%), tungsten (99.95wt.%), tantalum (99.95wt.%), niobium (99.95wt.%) and silicon (99.50wt.%). In order to ensure the melting efficiency and uniformity of alloy composition, the raw materials were mixed into blocks by pressing equipment before melting, and then melted in a sealed melting chamber. The controlled atmosphere in the melting chamber was dry high-purity argon (99.999%). Before heating, the melting chamber was evacuated to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
[0079] (S2) Preparation of titanium alloy: The alloy ingot is subjected to solution heat treatment (keeping at 1020°C for 2 hours, air cooling after being taken out of the furnace) and aging heat treatment (keeping at 700°C for 5 hours, air cooling after being taken out of the furnace) in sequence to obtain a titanium alloy.
[0080] The titanium alloy includes the following chemical compositions by mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, individual impurities ≤ 0.05%, total impurities ≤ 0.25%, and the rest is Ti. The β phase transition temperature is about 1040°C.
[0081] The titanium alloy prepared in this comparative example was subjected to microstructure observation and high-temperature mechanical property testing at 650°C.
[0082] After 1020℃ / 2h / air cooling, the thickness of the lamellar α phase is thicker than that after water cooling at the same temperature, and the content of the equiaxed α phase is higher, and the arrangement of the α / β lamellae is relatively neatly clustered; after further treatment at 700℃ / 5h / air cooling, nano-scale silicides are found to precipitate between the α / β lamellae.
[0083] The 650°C high temperature tensile yield strength and tensile strength are lower than those in Example 1, and the elongation after fracture is poor.
[0084] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a near-α titanium alloy, characterized in that: The following steps are involved: The alloy ingot is subjected to solution heat treatment and aging heat treatment in sequence to obtain a near-α titanium alloy; The near-alpha titanium alloy comprises the following chemical components in mass percentage: Al: 5.2-6.2%, Sn: 3.6-5.6%, Zr: 3.5-5.0%, Ta: 0.5-2.5%, W: 0.2-1.5%, Si: 0.2-0.6%, Nb: 0.2-0.5%, single impurity ≤ 0.05%, total impurities ≤ 0.25%, the rest is Ti; The solution heat treatment is used to dissolve all the nano-scale silicides in the alloy ingot into the titanium alloy matrix; The aging heat treatment is used to control the amount and distribution of nano-scale silicide precipitation.
2. The method for preparing a near-α titanium alloy according to claim 1, characterized in that: During the solution heat treatment process, the specific process is: keep warm at 1015-1025℃ for more than 2h, and water cool after taking out of the furnace.
3. The method for preparing a near-α titanium alloy according to claim 2, characterized in that: During the solution heat treatment process, the specific process is: keep warm at 1020℃ for 2h and water cool after taking out of the furnace.
4. The method for preparing a near-α titanium alloy according to claim 1, characterized in that: During the aging heat treatment process, the specific process is: keep warm at 695-705℃ for more than 5h, and air cool after leaving the furnace.
5. The method for preparing a near-α titanium alloy according to claim 4, characterized in that: During the aging heat treatment process, the specific process is: keep at 700℃ for 5h, and air cool after taking out of the furnace.
6. The method for preparing a near-α titanium alloy according to claim 1, characterized in that: The near-alpha titanium alloy includes the following chemical components in mass percentage: Al: 5.53%, Sn: 4.33%, Zr: 4.68%, Ta: 0.95%, W: 0.82%, Si: 0.44%, Nb: 0.41%, a single impurity ≤ 0.05%, a total impurity ≤ 0.25%, and the rest is Ti.
7. The method for preparing a near-α titanium alloy according to claim 1, characterized in that: The alloy ingot is prepared by the following method: Sponge titanium, aluminum, tin, sponge zirconium, tungsten, tantalum, niobium and silicon are pressed into a mixed block, and heated and melted in a sealed melting chamber to obtain an alloy ingot.
8. The method for preparing a near-α titanium alloy according to claim 7, characterized in that: Before heating, evacuate the melting chamber to a pressure of 10 -2 Pa and backfilled with argon three times to minimize the oxygen content.
9. A near-alpha titanium alloy prepared by the method according to any one of claims 1 to 8.
10. Use of the near-alpha titanium alloy according to claim 9 in the preparation of aerospace materials.
Citation Information
Patent Citations
Silicide of high-temperature titanium alloy and control method for precipitation growth of silicide
CN116144980A